Factors Influencing Long-Term Blood Flow in Extracranial-to-Intracranial Bypass for Symptomatic Internal Carotid Artery Occlusive Disease: A Quantitative Study. Issue 4 (26th April 2022) - Murai, Yasuo; Sekine, Tetsuro; Ishisaka, Eitaro; Tsukiyama, Atsushi; Kubota, Asami; Matano, Fumihiro; Ando, Takahiro; Nakae, Ryuta; Morita, Akio
Abstract : BACKGROUND: Maintaining the patency of extracranial-to-intracranial (EC-IC) bypass is critical for long-term stroke prevention. However, reports on the factors influencing long-term bypass patency and quantitative assessments of bypass patency are limited. OBJECTIVE: To quantitatively evaluate blood flow in EC-IC bypass using four-dimensional (4D) flow magnetic resonance imaging (MRI) and investigate factors influencing the long-term patency of EC-IC bypass. METHODS: Thirty-six adult Japanese patients who underwent EC-IC bypass for symptomatic internal carotid or middle cerebral artery occlusive disease were included. We examined the relationships between decreased superficial temporal artery (STA) blood flow volume and perioperative complications, long-term ischemic complications, patient background, and postoperative antithrombotic medications in patients for whom STA flow could be quantitatively assessed for at least 5 months using 4D flow MRI. RESULTS: The mean follow-up time was 54.7 ± 6.1 months. One patient presented with a stroke during the acute postoperative period that affected postoperative outcomes. No recurrent strokes were recorded during long-term follow-up. Two patients died of malignant disease. Seven cases of reduced flow occurred in the STA, which were correlated with single bypass ( P = .0294) and nonuse of cilostazol ( P = .0294). STA occlusion was observed in 1 patient during the follow-up period. Hypertension, age, smoking, dyslipidemia, and diabetes mellitus were not correlated with reduced blood flow in the STA. CONCLUSION: Double anastomoses and cilostazol resulted in long-term STA blood flow preservation. No recurrence of cerebral infarction was noted in either STA hypoperfusion or occlusion cases. Abstract :